Peter Schultz and Ralf Von den Hoff (eds). Structure, Image, ornament: architectural sculpture in the Greek world - Allen , Ruth (Journal of Greek Archaeology, 2016)
Greek (and Roman) architectural sculpture has frequently suffered reductive treatment from scholars. Either it has been broken up into stand-alone artworks divorced from their original display-contexts and studied only for what they can tell us of the development of style and subject, or it has been treated as ancillary to the building, or, in the case of temples, preparatory to the worshipper’s experience of the statue inside. This is in part a matter of historiography: the removal and display by Grand Tourists of sculptural features such as the Parthenon and Bassai friezes only encourages this kind of looking. It is also in part a matter of logistics: architectural sculpture was always hard to see, and the use of photography to aid its modern study not only separates the sculpture from its setting even further but also magnifies and flattens it, transforming a three-dimensional object into a two-dimensional picture.